PESERTA DIDIK DALAM PENDIDIKAN ISLAM: MEMBANGUN GENERASI BERAKHLAK MULIA - Mukmin, Mukmin (AZKIYA, 2023)
This article discusses the importance of Islamic education in shaping the character and noble character of students. Islamic education, with its holistic approach, focuses not only on academic aspects, but also on spiritual and moral development. The article highlights how Islamic education can create a generation with noble character through the application of inspiring learning methods, consistent character building, and the important role of educators who serve as role models. In addition, the article emphasizes the importance of cooperation between family, school and community in supporting this educational process. With a comprehensive approach, Islamic education is expected to produce individuals who are intellectually intelligent and have high moral awareness, so that they are able to face the challenges of the times and contribute positively to society.